1996
DOI: 10.1016/s0896-6273(00)80197-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Structural and Functional Components of Synaptic Plasticity. I. Fasciclin II Controls Synaptic Stabilization and Growth

Abstract: The glutamatergic neuromuscular synapse in Drosophila forms and differentiates into distinct boutons in the embryo and grows by sprouting new boutons throughout larval life. We demonstrate that two axons form approximately 18 boutons on muscles 7 and 6 by hatching and grow to approximately 180 boutons by third instar. We further show that, after synapse formation, the homophilic cell adhesion molecule Fasciclin II (Fas II) is localized both pre- and postsynaptically where it controls synapse stabilization. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
421
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(441 citation statements)
references
References 37 publications
16
421
2
2
Order By: Relevance
“…3). This result is in accord with the correlation between bouton number and muscle size observed in D. melanogaster throughout larval development and reflects the fact that as muscles increase in size they require more neurotransmitter release from presynaptic motor terminals to drive their contraction (11). Nonetheless, the value of r 2 for the correlation between bouton number and muscle size for NMJ4 among the different species (Fig.…”
Section: Nmj Morphology Shows Extensive Phenotypic Variation Amongsupporting
confidence: 85%
“…3). This result is in accord with the correlation between bouton number and muscle size observed in D. melanogaster throughout larval development and reflects the fact that as muscles increase in size they require more neurotransmitter release from presynaptic motor terminals to drive their contraction (11). Nonetheless, the value of r 2 for the correlation between bouton number and muscle size for NMJ4 among the different species (Fig.…”
Section: Nmj Morphology Shows Extensive Phenotypic Variation Amongsupporting
confidence: 85%
“…1C). Using a different fly muscle-specific driver, Mhc-Gal4 (22), to target skd mRNA, we observed that Mhc>skd RNAi flies also displayed increased total triglycerides (Fig. 1D).…”
Section: Resultsmentioning
confidence: 98%
“…As discussed above, synapse stability and synapse expansion during muscle growth at the NMJ are regulated by changes in FasII expression at pre-and postsynaptic membranes, and FasII expression is in part controlled by electrical activity (Schuster et al, 1996b;Ashley et al, 2005). One mechanism through which electrical activity alters FasII levels is by regulating its synaptic clustering via CaMKII-dependent phosphorylation of Dlg (Thomas et al, 1997;Koh et al, 1999).…”
Section: Ras/mapkmentioning
confidence: 99%
“…FasII has been shown to behave as a signaling molecule in early development (Garcia-Alonso et al, 1995) and to be required for memory formation in the adult (Cheng et al, 2001). In the complete absence of FasII, synapses initially form but retract early in development suggesting an essential role in NMJ maintenance (Schuster et al, 1996b). Alterations in the level of FasII during development have profound consequences for the structure and function of the synapse.…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
See 1 more Smart Citation